2016
DOI: 10.1590/0103-6440201601002
|View full text |Cite
|
Sign up to set email alerts
|

On the Causality Between Dentinal Defects and Root Canal Preparation: A Micro-CT Assessment

Abstract: This study aimed to evaluate the cause-effect relationship between canal preparation with ProTaper Universal (PTU) system and dentinal defects formation using micro-computed tomography (micro-CT) analysis. Forty mesial canals of mandibular molars with a type II Vertucci's canal configuration were scanned at an isotropic resolution of 14.16 µm. The sample was assigned to an experimental (n = 30) and a control (n = 10) groups, and the mesial canals were prepared with PTU system up to F2 instrument. The specimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
66
0
6

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(75 citation statements)
references
References 23 publications
3
66
0
6
Order By: Relevance
“…The results confirmed though the reliability of this contemporary technology for detecting dentinal defects as no single defect observed in the stereomicroscopy was undetected by the micro‐CT (De‐Deus et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…The results confirmed though the reliability of this contemporary technology for detecting dentinal defects as no single defect observed in the stereomicroscopy was undetected by the micro‐CT (De‐Deus et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…, , De‐Deus et al . , , Silva et al . ), because micro‐CT is based on a powerful X‐ray source, which allows visualization and measurement of the outer and inner structures of an opaque object without needing previous sample preparation or chemical fixation.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst studies using sectioning methods report a positive correlation between microcracks and routine endodontic procedures (Bier et al , Shemesh et al , Liu et al ), studies using a nondestructive imaging technology (high‐resolution micro‐computed tomography [micro‐CT]) have concluded that dentinal microcracks in extracted teeth are not caused by canal procedures (De‐Deus et al . , , , , , Zuolo et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, control groups of cross‐sectional studies are usually unable to detect microcracks, whereas thousands of microcracks are observed in the pre‐instrumented controls using micro‐CT technology (De‐Deus et al . , , , , , Zuolo et al ). Oddly enough, in three sectioning studies, dentinal defects were also found in the untreated control groups (Barreto et al , Bürklein et al , Coelho et al ).…”
Section: Introductionmentioning
confidence: 99%